Literature Study: Integration of Climate Change Education in School Curriculum of Various Countries - Septiani, Endah; Setyowati, Dewi Liesnoor; Juhadi, Juhadi; Husain, Fadly; Putri, Raudya Setya Wismoko (Universitas Negeri Semarang, 2024)
. In recent decades, climate change has become a pressing global issue, demanding effective educational approaches to increase awareness and mitigation actions. Facing the increasingly impactful issue of climate change, it is necessary to integrate climate change in education. So far, from searches on Google Scholar, many articles from overseas research have been published on the integration of climate change education in the school curriculum. This literature study aims to explore climate change models that are integrated into foreign curricula. The keywords used in the database search were developments in climate change education published in the last 5 years, namely the period 2020 to 2024. The method used in the literature study used PRISMA guidelines with four stages, namely identification, screening, feasibility and inclusion. Conclusions are drawn qualitatively. The database from Google Scholar was systematically analyzed to search for relevant climate change education development studies. There are seven articles that describe the integration of climate change education abroad. The research results show that there are significant variations in approaches to climate change education, ranging from the integration of climate change material into the curriculum to the development of special programs that focus on adaptation and mitigation. Therefore, it is necessary to carry out development research to create a more effective and sustainable climate change education model for the curriculum in Indonesia.